Training Process Structure of Highly Skilled Players in Mini-Football during the Competitive Period - Wang Leibo; Gennadii Lisenchuk; Ivan Stasiuk; Arkadiusz Marzec; Gennadii Zhigadlo; Vitalii Leleka; Konstantin Bogatyrev; Viktor Derkach; Oksana Adamenko; Oleg Slavitiak (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2021)
According to the competition calendar, a one-cycle training process for highly skilled mini-football players in the annual macrocycle was selected. Participants: 15 players of the First League of Ukraine in the futsal mini-football team "Fortetsya" (Kamianets-Podilskyi City), among them 1 player - Honored Master of Sports, 1 - Master of Sports of International Class, 4 - Candidate to Master of Sports, 9 - players of 1st rank. In the competitive period, non-specific means of highly skilled players in mini-football amounted to 40.2%, specific means - 59.8%, including special-prepa- ratory - 6.6%, leading - 30.9% and competitive - 22.3%. Aerobic loads ranged from 40.3 (4-day inter-cycle micro-cy- cle) to 53.6% (4-day competitive micro-cycle) during competitive and inter-gaming micro-cycles of this period. The use of mixed (aerobic-anaerobic) loads in the competitive period of futsal players training ranged from 45.0 (7-day inter-game micro-cycle) to 53.1% (4-day inter-game micro-cycle). The ratio of training means during the competitive period, the volume of training loads of different orientation in micro-cycles of competitive mezocycles of prepara- tion, the ratio of training loads of different orientation: aerobic (49.2%); mixed (46.1%); anaerobic alactatic (2.4%); anaerobic glycolytic (2.3%) have been identified. Taking into account the structure and content of a single-cycle variant of training process structure for the players of the first league team of Ukraine, the volumes of training loads of different orientation, the ratio of the training means of the players in the competitive period were determined.